Impactos socioeconômicos da Silvicultura na microrregião do Suaçuí - Carvalho, Luciano Pereira (2009)
The micro-region of Suaçuí river basin in the Vale do Rio Doce, east of the State of Minas Gerais, Brazil, has a landscape marked by large areas of monoculture eucalyptus plantations, which were started in the 1970, through tax incentives to reflorestation activities. Such reforestation has been strongly criticized by the rural population of the region and also by environmental organizations because of its social and environmental impacts. Otherwise, reforesting companies state that such impacts are justified by employment and income generation in the cities involved, once the reforested activity is the main provider of jobs and riches for the region. This paper discusses reforestation as a project for the development of the Rio Doce region, specifically the homogeneous micro-region of the Suaçuí river. The reforestation issue in this region involves social, economic and environmental impacts. The model of creating nationwide policies and public actions disregarding the region in question has been shown to be inefficient for employment generation and income distribution. In the specific case of the Suaçuí river micro-region, it is clear that reforestation was not important for generation jobs and income, as was the occupation of land. And as companies intensify mechanization in agriculture, the importance of the latter in generating jobs tend to decrease.